2007
DOI: 10.1016/j.paid.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ performance on delay and probability discounting tasks: Contributions of age, intelligence, executive functioning, and self-reported externalizing behavior

Abstract: Healthy adolescents, ages 9-23, completed delay and probability discounting tasks and measures of verbal and nonverbal intelligence, executive functioning, and self-reported internalizing and externalizing behavior. Delay but not probability discounting decreased with age. Delay discounting was also associated with verbal intelligence and Go-NoGo and Iowa Gambling Task performance. Probability discounting was associated only with externalizing behavior. Findings conform to an accumulation of evidence that whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
177
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(207 citation statements)
references
References 36 publications
28
177
2
Order By: Relevance
“…However, TD has been found to be associated with these individual characteristics by many others. First, age effects on TD have been found consistently in both real and hypothetical monetary TD tasks (Green et al, 1994;Olson et al, 2007;Scheres et al, 2006;Steinberg et al, 2009). However, Reynolds (2006) suggests that real TD tasks may be better suited for use with children because the choices are less abstract compared to hypothetical TD tasks.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, TD has been found to be associated with these individual characteristics by many others. First, age effects on TD have been found consistently in both real and hypothetical monetary TD tasks (Green et al, 1994;Olson et al, 2007;Scheres et al, 2006;Steinberg et al, 2009). However, Reynolds (2006) suggests that real TD tasks may be better suited for use with children because the choices are less abstract compared to hypothetical TD tasks.…”
Section: Discussionmentioning
confidence: 95%
“…We estimated full scale IQ on the basis of four subscales of the WISC-III, but we were not able to extract an estimate of the verbal and performal IQ. Olson et al (2007) suggested that the association between IQ and TD is driven solely by verbal aspects of intelligence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation is offered in the meta-analysis by Shamosh & Gray (2008), which showed that taking into account non-verbal intelligence resulted in only a slight increase in the relationship between intelligence and temporal discounting. We can therefore assume that high verbal intelligence is what primarily facilitates the use of verbal strategies helping to maintain self-control (Olson, Hooper, Collins & Luciana, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Seven of them used variations very similar to the original task in which there were small changes in the amount of the loan, gains and punishments after the choices 17,28,31,32,36,40,44 . Five used only the Children Gambling Task, proposed by Kerr and Zelazo 3,34,45,53,55 .…”
Section: Amongmentioning
confidence: 99%